Relationship Between Cytokines in Ascites and the Severity of Ovarian Hyperstimulation Syndrome: A Case Report - Ming-Tzeung Chung; Shao-Pai Wu (Elsevier, 2004)
Objective: Determination of the correlation of interleukin-1 (IL-1), IL-6, IL-8, tumor necrosis factor (TNF), and vascular endothelial growth factor (VEGF) levels in serum and ascites with the severity of ovarian hyperstimulation syndrome (OHSS). Case Report: We present the case of a woman with primary infertility who was enrolled in an ovulation induction program. OHSS developed 6 days after artificial insemination with the husband's sperm. We performed continuous paracentesis and recorded daily concentrations of IL-1, IL-6, IL-8, TNF, and VEGF in serum and ascites in an attempt to determine their correlation with the severity of OHSS. Conclusion: Improvement in symptoms and a decreasing amount of ascites were correlated with a decreasing serum concentration of VEGF.